Importance of the Precautionary Principle With Regard to the Risk of Exposure to Aerosols Containing Viral Loads of SARS-CoV-2 Present in Feces: In Perspective - Massicotte, Richard; Assanta, Mafu Akier; Rosette, Kakese Mukosa (Frontiers in Public Health, 2022)
In COVID-19 infection, the emissions of droplets and aerosols produced by the respiratory tract of contaminated subjects may represent a high risk of spreading the SARS-COV-2 virus in the environment. Thus, studies have shown that there is, at least, another source of droplets and aerosols in which viral particles of SARS-COV-2 can be found. It happens after flushing of toilet to dispose of the stools of a patient who has contracted COVID-19. The presence of viral particles of SARS-COV-2 in the stool could be linked to the concentration of angiotensin-converting enzyme 2 (ACE2) found on the surface of intestinal cells. Therefore, there is a reason to wonder whether the emission of viral particles by activating a toilet flush could represent an important potential risk of contamination for health care workers. To investigate this hypothesis, we have correlated different studies on the production of droplets and aerosols as well as the presence of viral particles following flush of toilet. This pooling of these studies led to the following conclusion: the precautionary principle should be applied with regard to the potential risk represented by viral particles of SARV-COV-2 in the stool when flushing the toilet.